Sex Differences in Film Induced Emotion: A Narrative Review - Sarika A, Dr. Sonia George (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Humankind has been fascinated by perceived differences between men and women .There are several empirical literature on sexual differences in emotion .Film is considered as one of the most effective method to induce emotions in a laboratory settings. In this study, the sex -emotion debate from the results of 24 studies which induced emotions using films in experimental settings were analysed. The differences in expressive, experiential, and physiological emotional responses of men and women collected from the studies were assessed and the key findings across three dimensions: (a) overt actions; (b) subjective reports, and (c) physiological activity were summarized.